Penentuan Lokasi Pengganti Kelurahan X Melalui Metode Analytical Hierarcy Process - Fauziah, Rizki; Umanto, Umanto (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2025)
This study aims to determine a new location for the Kelurahan X Office in North Jakarta using the Analytical Hierarchy Process (AHP) as a decision-making tool for multi-criteria analysis. The need for relocation arises due to the expiration of the land-use agreement between the Provincial Government of DKI Jakarta and the Indonesian Navy (TNI AL). The research adopts a mixed-method approach-both qualitative and quantitative-through literature review, field observation, and interviews with stakeholders. AHP was employed to evaluate three main criteria-environment, accessibility, and cost-which were further broken down into nine sub-criteria. Three alternative locations were analyzed: Model 1 (Jl. JA 1), Model 2 (Jl. BGR), and Model 3 (Jl. GK). The analysis results indicate that Model 1 received the highest score of 63.49%, making it the most optimal location. This study demonstrates that AHP is effective in supporting data-driven, objective, and participatory decision-making processes in the context of public service planning. Despite limitations such as a restricted number of alternatives and potential subjectivity in assessments, this research makes a significant contribution to urban spatial planning and can serve as a model for similar projects in other urban area.